2021
DOI: 10.1002/1878-0261.13051
|View full text |Cite
|
Sign up to set email alerts
|

PRRX1 induced by BMP signaling decreases tumorigenesis by epigenetically regulating glioma‐initiating cell properties via DNA methyltransferase 3A

Abstract: Glioma-initiating cells (GICs), a major source of glioblastoma recurrence, are characterized by the expression of neural stem cell markers and the ability to grow by forming non-adherent spheres under serum-free conditions. Bone morphogenetic proteins (BMPs), members of the transforming growth factor- family, induce differentiation of GICs and suppress their tumorigenicity.However, the mechanisms underlying the BMP-induced loss of GIC stemness have not been fully elucidated. Here, we show that paired related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…BMPs regulate expression of various target genes in glioma-initiating cells. In this figure, the roles of PRRX1 ( Tanabe et al, 2022 ) and gremlin1 ( Yan et al, 2014 ) are shown. Of the two splice isoforms of PRRX1, only pmx-1b induces differentiation of glioma-initiating cells.…”
Section: Effect Of Bone Morphogenetic Proteins On Cancer Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…BMPs regulate expression of various target genes in glioma-initiating cells. In this figure, the roles of PRRX1 ( Tanabe et al, 2022 ) and gremlin1 ( Yan et al, 2014 ) are shown. Of the two splice isoforms of PRRX1, only pmx-1b induces differentiation of glioma-initiating cells.…”
Section: Effect Of Bone Morphogenetic Proteins On Cancer Stem Cellsmentioning
confidence: 99%
“…We found that the expression of paired related homeobox 1 (PRRX1) is induced by BMPs in glioma-initiating cells. The longer isoform of PRRX1, pmx-1b, interacts with DNA methyltransferase 3A (DNMT3A) and induces promoter methylation of the PROM1 gene encoding CD133, thereby attenuating stem cell-like properties ( Tanabe et al, 2022 ) ( Figure 3 ). We have also reported that the tyrosine kinase Eph receptor A6 (EPHA6) promotes apoptosis in BMP-2-sensitive glioma-initiating cells ( Raja et al, 2019 ).…”
Section: Effect Of Bone Morphogenetic Proteins On Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain gliomas are the most common primary malignant tumors in the central nervous system, presenting with an increasing mortality rate. Several patients present with an OS time of less than 2 years ( Mondal and Kulshreshtha, 2021 ; Petridis et al, 2021 ; Tanabe et al, 2021 ; Tu et al, 2021 ). Wang et al (2020c) found that the upregulation of LINC01116 in glioma cells is related to poor prognosis.…”
Section: Expression and Clinical Characteristics Of Linc01116 In Various Cancer Typesmentioning
confidence: 99%
“…Whereas both isoforms of this protein can bind to the PROM1 promoter, only the long isoform (PRRX1A) with OAR (otp, aristaless, and rax) domain in its C-terminal region (PRRX1A) interacts with DNMT3A and induces PROM1 promoter P1 methylation. Both PRRX1A and DNMT3A silencing increase CD133 + positive subpopulation even in the presence of BMP-4 and enhance their tumorigenic capacity [ 54 ].…”
Section: Cd133: Structure Localization and Posttranslational Modifica...mentioning
confidence: 99%